Autoantibodies and immunoglobulins in collagenous colitis. Issue 1 (July 1996) - Bohr, J; Tysk, C; Yang, P; Danielsson, D; Järnerot, G
Abstract : BACKGROUND: The aetiology and pathogenesis of collagenous colitis are unknown. Autoimmunity has been suggested, but no serological findings have supported such a theory. AIMS AND METHODS: Serum from 38 collagenous colitis patients and 38 matched healthy controls was analysed for autoantibodies--that is, antinuclear antibodies, antineutrophil cytoplasmic antibodies, smooth muscle and mitochondrial antibodies, rheumatoid factor and antibodies to thyroglobulin and microsomal antigen, together with antibodies to endomysium, gliadin, and cardiolipin. The serum values of IgA, IgG, IgM, and IgG-subclasses, and complement factors C3 and C4 were also determined. RESULTS: In patients with collagenous colitis the mean value of IgM was significantly increased 2.5 g/l (95% CI; 1.9, 3.2) compared with 1.4 g/l (95% CI; 1.2, 1.7) in controls (p = 0.002). Antinuclear antibodies occurred in nine of 38 patients compared with three of 38 controls, this difference was not statistically significant (p = 0.11). The results of all other immunoglobulins, complement factors, and specific antibodies showed no statistical difference between patients and controls. CONCLUSIONS: No firm evidence for an autoimmune genesis in collagenous colitis is found in this study, although the findings of a positive ANA-titre in some patients and an increased IgM level might give some support for this hypothesis.